EMANCIPATORY INTERPRETATION: STRATEGICAL UNDERSTANDING OF THE QUR’ANIC MORAL MESSAGE FOR LIFE - Ahmad Hasan Ridwan; Irfan Syafrudin; Zaki Ahmad Mubarok (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2020)
This study discusses the emancipatory interpretation of Qur’anic verses using critical reflection to gain moral aspects of the Qur’anic messages. This emancipatory interpretation aims at sharpening conscience awareness in seeing, perceiving, and solving social, humanitarian problems. This research aims to answer the notion of emancipatory interpretation on a philosophical basis and its application to answer contemporary problems. This study employs a qualitative method with literary studies to gather and interpret the data. This study shows that the principle of emancipatory interpretation includes examining the scriptural text linguistically, and then understand it philosophically. In the context of praxis, the messages derived from the text should be investigated on the ethical liberation spirit that can be reflected in human life. To gain this ethical liberation of the revelation can be understood by revealing the implicit significance of the Qur'anic text connected with the social issues in social reality to solve the problems. Emancipatory interpretation is expected to answer contemporary social problems like poverty, underdevelopment, injustice, political crimes, corruption, collusion, nepotism, labor, and gender discrimination.